Determinant of life insurance demand in Ethiopia - Mohammed Meko; Kenenisa Lemie; Abel Worku (Universitas Hayam Wuruk Perbanas, 2018)
Life Insurance plays an important role to insure against lifetime uncertainty resulting for the mortality risk of individual. Even though the performance of insurance industry contributes to smooth operation of the nationâ€™s economy, the industry in general and life insurance in particular is at its low level of development in Ethiopian context. This study therefore, is aimed at investigating the determinants of life insurance demand in Ethiopia. The study used balanced panel data model to examine the determinants of life insurance demand usingdata collected from four insurance companies for sixteen years, from 2001-2016. Random effect model was usedto analyze the data using STATA version 13 software. The study used life insurance density as dependent variable and seven independent variables that are income, inflation, real interest rate, life expectance, age dependence ratio, price of insurance and urbanization. The regression result show that real interest rate, life expectancies, age dependency ratio, urbanizationÂ and inflation show positive and significant effect at 1% and 5% significance level on life insurance demand in Ethiopia, whereas GDP per capita and price of insurance has insignificant effectÂ on life insurance demand in Ethiopia.Urbanization is the most important factor that influences demand for life insurance followed by life expectance, age dependency ratio and Inflation. Real interest rate is the least important factor in influence demand for life insurance. The concerned insurance companies are recommended to consider these factors in marketing their life insurance products.